Hubungan Pengetahuan Orang Tua Dengan Perilaku Kekerasan Verbal Pada Anak - Leony Manggivera Indika; Dewi Rokhanawati (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2017)
This study aims to determine knowing the relationship of parental knowledge with verbal abuse behavior in children at Kindergarten ABA Tegalrejo, 2017. This study used a correlation study with cross sectional time approach. Methods of data collection using primary data by using questionnaire. Respondents of this study consisted of 69 respondents, using purposive sampling technique of data analysis using Kendall Tau. Kendall Tau with a p value of 0.016 (p0.05), indicates that there is a relationship between parental knowledge with verbal violence behavior in children. Hopefully TK ABA Tegalrejo can cooperate with Puskesmas Tegalrejo inorder to conduct routine socialization activities related to verbal violence, so it can increase the insight of the guardian of the students.